TINJAUAN IMPLEMENTASI PRINSIP KOPERASI PADA KLUB SEPAK BOLA INDONESIA - Patron Natadjaya; Muhammad Fawwaz, Raihanto; Tiara Kania, Ladzuardini; Heriyaldi, Heriyaldi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Based on a survey conducted by Nielsen in 2014, 77% of the total population ofIndonesia was attracted to football clubs. This value shows that the football industryin Indonesia has large market potential. However, this potential has not been fullyutilized, since there are still clubs dispersion due to management problems. Thisstudy uses data sourced from World Football in the German League (Bundesliga),Spanish League (La Liga), English League (Premier League), and IndonesianLeague (Liga 1) in the 2018/2019 season. Cooperative principles are used to find outthe differences between football management. Furthermore, we used qualitative andquantitative analysis, in SWOT analysis, quadrant mapping, and trendline of thescatter plots to determine the relationship between variables studied. The resultshows a positive relationship between the two variables and concluded that leagueswith cooperative football clubs tend to have a positive slope and higher coefficientvariable points accumulation against the average variable audience compared to anon-cooperative club.